Independent Mixed Sampling Plans Potato Paste as The Main Raw Material for Biscuits at PT X - Sri Mumpuni Retnaningsih; Muhammad Alifian Nuriman; Rizka Widya Berliana (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
PT X, a prominent entity in the snack food manufacturing sector, has identified significant quality control challenges in the production of its flagship biscuit product, which utilizes potato paste as a key ingredient. The primary quality attributes under assessment are the color and pH level of the potato paste. Historically, inconsistencies in these attributes have been observed, resulting in substandard dough quality. The existing inspection methodology, characterized by its subjective nature due to the immediacy of processing requirements, has heightened the risk of accepting raw materials that do not meet established standards. To address this issue and enhance the evaluation of current inspection processes, an independent mixed sampling plans method is proposed. This method entails an initial sampling based on variable criteria followed by a secondary sampling based on attribute criteria if the initial sample is rejected. Utilizing the Dodge-Romig Table with a Lot Tolerance Percent Defective (LTPD) of 12% and a consumer risk of 10%, the study determined an Acceptable Quality Level (AQL) of 1.01% and a producer risk of 4%. The proposed sampling plan necessitates 7 samples for variable criteria and 31 samples for attribute criteria, with an acceptance number of one defect. Implementation of this method, based on company data, resulted in a revenue probability of 0.6933, indicating that 69 out of every 100 inspected units of potato paste would conform to quality standards. This proposed method significantly enhances the objectivity and reliability of the inspection process, thereby augmenting overall product quality.